2002
DOI: 10.1046/j.1365-2788.2002.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective judgements of quality of life: a comparison study between people with intellectual disability and those without disability

Abstract: The present study investigated the relationship between objective and subjective measures of quality of life (QoL), and in particular, health status and primary care services. Thirty-one people with intellectual disability (ID) were interviewed using a QoL questionnaire. Thirty-one matched controls from the general population filled in a parallel questionnaire. The results in both groups support the findings of many researchers which indicate that satisfaction with aspects of life is generally high (i.e. appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 22 publications
2
41
1
3
Order By: Relevance
“…A small sample study of preventive care and health promotion practices in the United Kingdom found that, compared with matched non-ID controls, persons with ID reported more preventive care and health promotion counseling in the past year (health check, blood pressure, eye, hearing, contraception/ sex, smoking, diet, alcohol, and exercise). However, for the controls, most care occurred in the general practitioner's office, while about one-half of the health promotion care for people with ID occurred outside of the general practitioner's office in the day center or local specialist hospital [Hensel et al, 2002]. A national U.S. study by the present authors also found that family practice and internal medicine physicians reported engaging less frequently in a range of health promotion practices for their patients with physical disabilities compared with patients without disabilities [Downs et al, 2004].…”
Section: Disparities In Preventive Care and Health Promotionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small sample study of preventive care and health promotion practices in the United Kingdom found that, compared with matched non-ID controls, persons with ID reported more preventive care and health promotion counseling in the past year (health check, blood pressure, eye, hearing, contraception/ sex, smoking, diet, alcohol, and exercise). However, for the controls, most care occurred in the general practitioner's office, while about one-half of the health promotion care for people with ID occurred outside of the general practitioner's office in the day center or local specialist hospital [Hensel et al, 2002]. A national U.S. study by the present authors also found that family practice and internal medicine physicians reported engaging less frequently in a range of health promotion practices for their patients with physical disabilities compared with patients without disabilities [Downs et al, 2004].…”
Section: Disparities In Preventive Care and Health Promotionmentioning
confidence: 99%
“…This difference in health status is particularly evident for people with more severe disabilities and is observed across the typical measures used for population comparisons. Health disparities for people with ID have been documented in mortality [Hollins et al, 1998;Durvasula and Beange, 2001;Bittles et al, 2002], morbidity [Beange et al, 1995;Janicki et al, 1999], and quality of life [Hensel et al, 2002].…”
mentioning
confidence: 99%
“…They found scores of life satisfaction in persons with ID higher than expected and similar to those of the general population. This data could be explained in terms of low expectations, little choice, lack of experience 40 , and, as previously mentioned, low sensitivity of self wellbeing assessments, the latter due to an inner affective/cognitive homeostatic system, which would tend to be maintained at normative levels 20 . "Being Psychological" came out to be very low in the group with ID: this is an important fact, because this aspect is not always properly estimated.…”
Section: Self-reported Experiences and Satisfaction In Persons With Smentioning
confidence: 84%
“…Self-rating procedures are sensitive to how questions are framed (cf., Hertzog et al, 2000), but they also are sometimes related to objective measures of performance (Maylor, 1990). Aspirations, preferences and opportunities for individual choice are linked to self-ratings which may be why individuals without intellectual disability and individuals with intellectual disability make similar ratings (Hensel, Rose, Kroese, & Banks-Smith, 2002). That is, the self-rating and the experience of your own performance may depend on whom you consider relevant to compare with as well as to what extent you notice and remember your omissions.…”
Section: Prospective Memory and Intellectual Disability 19 19mentioning
confidence: 99%